Combining IL-2-based immunotherapy with commensal probiotics produces enhanced antitumor immune response and tumor clearance. Issue 2 (7th October 2020) - Shi, Linlin; Sheng, Jianyong; Chen, Guozhong; Zhu, Peng; Shi, Changping; Li, Bei; Park, Chaiwoo; Wang, Jingyi; Zhang, Bixiang; Liu, Zhi; Yang, Xiangliang
Abstract : Background: Interleukin-2 (IL-2) serves as a pioneer of immunotherapeutic agent in cancer treatment. However, there is a considerable proportion of patients who cannot benefit from this therapy due to the limited clinical responses and dose-limiting toxicities. Mounting evidence indicates that commensal microbiota shapes the outcome of cancer immunotherapies. In this study, we aim to investigate the enhancing effect of Akkermansia muciniphila (AKK), a beneficial commensal microbe receiving considerable attentions, on the antitumor efficacy of IL-2 and explore the underlying molecular mechanism. Methods: Colorectal carcinoma patient-derived tumor tissues were used to evaluate the therapeutic efficacy of combination treatment. AKK was orally delivered to B16F10 and CT26 tumor-bearing mice along with systemic IL-2 treatment. Flow cytometry was carried out to analyze the tumor immune microenvironment. The molecular mechanism of the enhanced therapeutic efficacy was explored by RNA-seq and then verified in tumor-bearing mice. Results: Combined treatment with IL-2 and AKK showed a stronger antitumor efficacy in colorectal cancer patient-derived tumor tissues. Meanwhile, the therapeutic outcome of IL-2 was significantly potentiated by oral administration of AKK in subcutaneous melanoma and colorectal tumor-bearing mice, resulting from the strengthened antitumor immune surveillance. Mechanistically, the antitumor immune response elicited by AKK was partially mediated by Amuc, derived from the outer membrane protein of AKK, through activating toll-like receptor 2 (TLR2) signaling pathway. Besides, oral supplementation with AKK protected gut barrier function and maintained mucosal homeostasis under systemic IL-2 treatment. Conclusion: These findings propose that IL-2 combined with AKK is a novel therapeutic strategy with prospecting application for cancer treatment in clinical practice.